Do relatório de gestão ao relato integrado: o caso do Ministério da Fazenda - Miranda, Gelciene Barbosa de (Universidade Federal do Tocantins, 2021)
The Integrated Reporting was developed by the International Integrated Reporting Council (IIRC) formed by an international alliance of companies, regulators, investors, standardization bodies, accounting entities and academia that proposes a new approach to the reporting process, combining financial and non-financial information. The objective of this work is to show the evolution of the content of the management report of the Ministry of Finance of Brazil, after adopting the premises of the integrated report. A content analysis of the management reports of the Ministry of Finance from 2015 to 2018 was carried out. As a result, it was observed that the Ministry of Finance adhered to the Integrated Reporting Framework. It was also found that in his speech the Ministry of Finance uses some of the behavioral dynamics pointed out by Suchman (1995), such as: responding to needs, demonstrating success, building reputation, communicating honestly, seeking to legitimize his actions before society. In addition, the results show how the Agency highlights its creation of value from the perspective of capital.